Tax planning: proposal for a prepared meal supply company (Revista Brasileira de Contabilidade e Gestão, 2022)
One way to reduce the tax expenditures of a company through legal provisions is through tax planning. This study has aimed to carry out tax planning and thus identify the most appropriate regime for a small enterprise located in a city in the north of Paraná, Brazil, whose activity is to provide prepared meals. The research is classified as exploratory, in terms of objectives, and as qualitative, in terms of approach, and it uses the case study in the methodological procedures. With the information from the financial statements provided by the company, a simulation has been performed with the three Brazilian tax regimes, simples nacional, presumptive profit, and taxable profit in order to verify which would be the least onerous regime. The analysis of the taxes complied with the current legislation of the regimes according to the company's branch of activity. The option for the simples nacional resulted in lower taxation, in this way ensuring the potentialization of the company's result and the generation of greater profit. However, an exorbitant difference can be observed in tax expenditures between the different types of taxation, which produce different percentages of profitability. The research has contributed theoretically to the area of ​​Tax Accounting, as it has used, as a sample, a field of activity still little explored in other studies.
Keywords: tributes; tax planning; case study; prepared meal company; financial accounting